2019
DOI: 10.1039/c9cc07982c
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effect of synthetic α-to-β3-amino acid mutations on the binding of phosphopeptides to 14-3-3 proteins

Abstract: Systematic α → β3 amino acid substitutions reveal a crucial role for native +2 proline residues in 14-3-3 binding peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The biological function of the 14–3–3 adapter proteins hinges on PPIs with its clients. Modulators of 14–3–3 are desired for mechanistic studies and for interference with pathology. , Inhibitory modulation of 14–3–3 PPIs is typically done with peptides and peptidomimetics derived from client partners. Simultaneously, supramolecular systems have been brought forward as 14–3–3 recognition elements. ,, A prominent client protein for 14–3–3 is exoenzyme S (ExoS), a pathogenicity factor of the pneumonia-causing bacterium Pseudomonas aeruginosa , which uses human 14–3–3 as a host factor. Here, we show for the first time the interfacing of a synthetic supramolecular element (molecular tweezers) with an ExoS peptide recognition motif to furnish a powerful ditopic 14–3–3 ligand.…”
mentioning
confidence: 99%
“…The biological function of the 14–3–3 adapter proteins hinges on PPIs with its clients. Modulators of 14–3–3 are desired for mechanistic studies and for interference with pathology. , Inhibitory modulation of 14–3–3 PPIs is typically done with peptides and peptidomimetics derived from client partners. Simultaneously, supramolecular systems have been brought forward as 14–3–3 recognition elements. ,, A prominent client protein for 14–3–3 is exoenzyme S (ExoS), a pathogenicity factor of the pneumonia-causing bacterium Pseudomonas aeruginosa , which uses human 14–3–3 as a host factor. Here, we show for the first time the interfacing of a synthetic supramolecular element (molecular tweezers) with an ExoS peptide recognition motif to furnish a powerful ditopic 14–3–3 ligand.…”
mentioning
confidence: 99%
“…With a large number of PPIs involving 14-3-3 (Johnson et al, 2010) identified as potential therapeutic targets, this approach can determine the structures of these complexes in a straightforward manner and therefore will assist greatly in the first steps of structure-based drug development, producing crystals from which structures can easily be determined and which can be used as a basis for soaking fragments/compounds (both inhibitors and stabilizers of 14-3-3 PPIs; Stevers et al, 2018;Ballone et al, 2018). So far, discovered small-molecule ligands of 14-3-3 proteins display a considerable degree of chemical diversity, ranging from fragments (Sijbesma et al, 2017(Sijbesma et al, , 2019 and 'classical' small molecules to supramolecular ligands (Bier et al, 2013(Bier et al, , 2017de Vink et al, 2017) and natural products (Andrei, de Vink et al, 2018;Kaplan et al, 2020;Molzan et al, 2013) to modified peptides (Glas et al, 2014;Andrei, Meijer et al, 2018;Milroy et al, 2015;Andrei et al, 2019), with most requiring specific co-crystallization conditions. Our new method may also enable a faster and more modular elucidation of these ligands in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57][58] Recent reports attest that significant alteration in the backbones influences activity and/or selectivity as well as binding properties in peptide-protein interactions. 34,59,60 Comparison of morphologies adopted by different αγ hybrid peptides and unnatural α-analogues revealed the dependence of assembly on the position and spatial arrangement of aromatic groups. 61,62 Interesting morphological changes were observed for αγ peptides when they were subjected to constitutional changes.…”
Section: Introduction To Self-assembly Of Hybrid Peptidesmentioning
confidence: 99%